Islam in a Scientific Perspective: An Interdisciplinary Study of Religion, Social and Culture (Case Study of the Luwur Kanjeng Sunan Kudus Valley) - Mohammad Khoirur Rozaq; Lailatur Robihah; Muhammad Miftah (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
Islam as an object of study and religious practice has broad dimensions, covering theological, social, and cultural aspects. The study of Islam in scientific discourse requires an interdisciplinary approach that combines various disciplines, such as religious studies, sociology, anthropology, and history, in order to understand the dynamics of Islam in the context of modern society. This study aims to explore how Islam is studied scientifically through various methodological approaches and to identify challenges and opportunities in interdisciplinary studies in the case study of the tradition of buka luwur kanjeng sunan kudus. By using qualitative methods in the form of literature reviews and critical analysis, this study found that an interdisciplinary approach allows for a more comprehensive understanding of Islam, both as a doctrine and as a socio-cultural phenomenon. The results of this study indicate that the integration of various disciplines in Islamic studies can enrich academic perspectives and provide deeper insights into the role of Islam in shaping the social and cultural life of society. Interdisciplinarity between culture and society in the case study of buka luwur kanjeng sunan kudus can improve cooperation and teach people to give alms. Meanwhile, interdisciplinary studies help us understand how religious practices can coexist with local traditions without losing their spiritual essence. Therefore, an interdisciplinary approach is a must in understanding Islam holistically and objectively in the academic realm.